The Role of Product Warranty in Building Customer Loyalty: A Case Study of The Indonesian Tire Industry - Saputra, Suyono; Josline, Josline (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study explores the strategic role of product warranty in fostering customer loyalty within the Indonesian automotive tire industry. Drawing on signaling theory, the research investigates both the direct and mediated effects of product warranty on loyalty through brand trust, customer satisfaction, and brand image. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with data collected from 323 respondents who had purchased tires from major global brands. The results confirm that product warranty has significant positive effects on all three mediators, which in turn strongly influence customer loyalty. Mediation analysis reveals that customer satisfaction and brand image are the most influential pathways. These findings highlight that warranties function not only as functional assurances but also as symbolic signals that shape post-purchase evaluations and brand commitment. The study contributes to the marketing literature by extending signaling theory in the context of high-involvement purchases in emerging markets. It offers practical insights for companies to leverage warranty programs as strategic assets that enhance trust, satisfaction, and long-term loyalty.